Conscientious objection and systemic injustice. (September 2020) - Pruski, Michal
This paper follows on from a brief debate about the role of conscientious objection in healthcare, where the issue arose as to whether conscientious objection is (or can) be a tool of resistance against systemic injustice. The paper contributes to this debate by highlighting that some authors generally opposed to conscientious objection in healthcare have shown some support to this idea. Perhaps if there is one area in which all can agree, it is that in healthcare conscientious objection should be allowed so as to prevent cases of systemic injustice.